Pursuing Precise Vehicle Movement Trajectory in Urban Residential Area Using Multi-GNSS RTK Tracking - Sun, Q.; Xia, J.; Foster, J.; Falkmer, Torbjorn; Lee, H. (2017)
© 2017 The Authors. Published by Elsevier B.V. Close-to-reality vehicle movement trajectory data can be useful in many transport and geography studies when precise vehicle localization or timing is required in the application. Vehicle kinematic tracking by GPS (Global Positioning System) varies in the data accuracy depending on some factors such as the receiver capability, satellites availability. Nevertheless, advanced positioning techniques offer possibilities to enhance the tracking data quality. In this paper, the high performance of multi-GNSS (multiple Global Navigation Satellite Systems) with Real-time Kinematic (RTK) solution was investigated aiming to pursue precise vehicle movement trajectory in an urban residential area of Australia. We systematically compared vehicle kinematic recordings between different positioning solutions by multi-GNSS and GPS-only approaches. Different elevation cut-off angles ranging from 5 - 35° were applied to simulate satellites' availability in different sky view conditions. The results showed that the multi-GNSS approach outperformed conventional GPS positioning in availability and positioning accuracy, and RTK solution at 10Hz generated ideal vehicle movement trajectory suitable for driving behaviours studies.